2022
DOI: 10.1021/acsami.2c12936
|View full text |Cite
|
Sign up to set email alerts
|

Low Energy Switching of Phase Change Materials Using a 2D Thermal Boundary Layer

Abstract: The switchable optical and electrical properties of phase change materials (PCMs) are finding new applications beyond data storage in reconfigurable photonic devices. However, high power heat pulses are needed to melt-quench the material from crystalline to amorphous. This is especially true in silicon photonics, where the high thermal conductivity of the waveguide material makes heating the PCM energy inefficient. Here, we improve the energy efficiency of the laser-induced phase transitions by inserting a lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…If the heat of fusion were considered, we would expect the peak BCB temperature to be even lower when the MoS 2 layer is included because a greater proportion of the available energy is used by the melt-transition. Adding TMDCs at the waveguide-Sb 2 S 3 interface also has the added advantage that the Sb 2 S 3 phase transitions can be induced more efficiently [43]. Indeed, we note that with the MoS 2 layer included in the structure, the laser power required to reach the Sb 2 S 3 melting point was reduced by 23% to 20 mW.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…If the heat of fusion were considered, we would expect the peak BCB temperature to be even lower when the MoS 2 layer is included because a greater proportion of the available energy is used by the melt-transition. Adding TMDCs at the waveguide-Sb 2 S 3 interface also has the added advantage that the Sb 2 S 3 phase transitions can be induced more efficiently [43]. Indeed, we note that with the MoS 2 layer included in the structure, the laser power required to reach the Sb 2 S 3 melting point was reduced by 23% to 20 mW.…”
Section: Resultsmentioning
confidence: 90%
“…We suggest a novel solution to overcome the laser-induced damage to the BCB layer during amorphisation. Recently, Ning et al showed that two-dimensional (2D) transition metal dichalcogenides (TMDCs), such as MoS 2 and WS 2 , can be used as thermal barriers during amorphisation of PCMs on silicon waveguides [43]. These TMDCs confine the thermal energy within the PCM layer without significantly influencing the waveguide effective refractive index or the concomitant propagating mode.…”
Section: Resultsmentioning
confidence: 99%